Bright night sleeping environment induces diabetes and impaired glucose tolerance in non-human primates - Wang, Shuxing; Chen, Zhenyi; Liang, Zihao; Xu, Qiang; Zhang, Jiankai (Frontiers in Endocrinology, 2025)
BackgroundAccording to the IDF Diabetes Atlas regularly published by International Diabetes Federation, the prevalence of diabetes and impaired glucose tolerance (IGT), diabetes-related mortality and health expenditure are becoming serious eventually at the global, regional and national level. While the data alarm people, the exact cause remains unknown. It is widely accepted that glucose metabolism can be impaired by circadian rhythms disruption and sleep disturbances, both closely linked to exposure to light at night. However, there is little direct experiment on primates to study the precise extent of how serious bright sleeping environment at night impairs glucose metabolism, what the relationship is between nocturnal brightness and the development of diabetes and IGT, any difference between male and female, and whether aging and weight are involved. This study aims to address these questions in monkeys.MethodsIn a reduced daytime bright condition resembling human living rooms, 197 Cynomolgus (130 male, 67 female) were exposed to three distinct light intensities (13, 35, 75Lux) at night for consecutive ten months. Animals were retrospectively divided into four groups according to glucose metabolic status by the end of the experimental session, spontaneous diabetes mellitus (SDM, N=11), light-induced diabetes (LID, N=83), impaired fasting glucose tolerance (IFG, N=36), and normal glucose tolerance (NGT, N=67). Data pertaining to the glucose metabolism such as concentrations of fasting glucose, glycosylated hemoglobin, plasma insulin and C-peptide were collected monthly and analyzed.Results1) Bright night exasperated glucose metabolism in individuals with pre-existing diabetes, led to premature death; 2) Stronger white light intensity-dependently induced diabetes and IFG in previous healthy monkeys: the brighter the light, the quicker the metabolism disturbance and IFG developed, and also the higher morbidity of LID and IFG; 3) Exposure to nocturnal light had a synergistic impairing effect on glucose metabolism with aging and weight. 4) Female were more susceptible to night brightness.ConclusionsLight in sleeping environment exacerbates glucose metabolism in individuals with pre-existing diabetes, leads to IFG and diabetes in healthy primates. Moreover, the harmful effects of bright night on glucose metabolism are synergistic with aging and weight.